Red-Fleshed Apple Anthocyanin Extracts Attenuate Male Reproductive System Dysfunction Caused by Busulfan in Mice - Xu, Jihua; Zhang, Xiang; Sun, Xiaohong; Lv, Qiang; Zhang, Yugang (Frontiers in Nutrition, 2021)
In this research, we analyzed the effect of oral administration of red-fleshed apple anthocyanin extract (RAAE) on busulfan-treated mice. At first, we showed that the most abundant component in RAAE was cyanidin 3-O-galactoside. To determine the effect of RAAE, mice were divided into control and four different concentrations of RAAE feeding treatment groups (BA0, no RAAE; BA0.1, 0.1 mg/kg; BA1, 1 mg/kg; BA5, 5 mg/kg) following busulfan injection. We observed that RAAE treatments displayed ameliorative effects on male reproductive system dysfunction caused by busulfan, including recovering the irregular arrangements of seminiferous tubules, increasing the number of spermatogonia and spermatocytes, improving sperm concentration by three-fold in BA0.1 and improving sperm motility by two-fold in BA1. LC-MS/MS analysis showed significant up- or down-regulation of certain metabolites such as lysophosphatidylcholine (LysoPC), L-arginine, glycine, anandamide, and L-carnitine, which could contribute to the positive effects of RAAE, especially in PBA1 (plasma of BA1) and PBA5 (plasma of BA5). Taken together, our results indicate that 1 mg/kg of RAAE is a suitable concentration for rescuing spermatogenesis in mice. Our research suggests that RAAE could be a potential nutraceutical for protecting spermatogenesis after busulfan therapy in cancer.